1989
DOI: 10.1148/radiology.172.1.2662248
|View full text |Cite
|
Sign up to set email alerts
|

Incidental fibromuscular dysplasia in potential renal donors: long-term clinical follow-up.

Abstract: The clinical natural history of renal arterial fibromuscular dysplasia (FMD) in patients with normal blood pressure is unknown, to the authors' knowledge. The authors reviewed the results of 1,862 renal angiograms obtained in potential renal donors. FMD was present in 71 patients (3.8%). The average age at which FMD was discovered was 50.8 years. Seventy-five percent of the patients with FMD were female. Of 30 patients who did not undergo nephrectomy, eight (26.6%) developed hypertension over a mean followup i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 0 publications
1
63
3
2
Order By: Relevance
“…The natural history of FMD in a large number of asymptomatic, normotensive potential donors is not well defined. Since FMD can progress it is possible that undetected mild stenosis after donation may progress and cause hypertension and compromise the function of the solitary kidney of the donor (8,13,14,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural history of FMD in a large number of asymptomatic, normotensive potential donors is not well defined. Since FMD can progress it is possible that undetected mild stenosis after donation may progress and cause hypertension and compromise the function of the solitary kidney of the donor (8,13,14,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In a large study by Cragg et al, 1862 renal angiograms in potential donors showed 71 cases of FMD (3.8%). These patients with FMD and normal blood pressure were followed for the natural course of the disease for many years (8). Among these patients, 26.6% of the 30 patients who did not undergo nephrectomy developed hypertension over 7.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of authors (75%) reporting on donation from LDs affected by FMD [1,[3][4][5][6][7][10][11][12][13][14][15] account for a maximum of 3 cases.…”
Section: Resultsmentioning
confidence: 99%
“…While the prevalence of renal arterial FMD in autopsy studies has been only approximately 1%, 3,26 renal artery FMD has been reported in 3.5% of potential living renal transplant donors, 27 who would have been carefully studied, bringing into question the true prevalence of FMD. Similarly, while severe ␣ 1 -AT deficiency (PiZZ phenotype) is considered rare, partial deficiency (PiMS and PiMZ phenotypes) has been described in 10% to 15% of the Australian population 14,15 and was present in 12% of patients in the present study.…”
Section: Discussionmentioning
confidence: 99%